LOVE YOURSELF: A SUCCESSFUL TRENDING CAMPAIGN IN BUILDING SELF-ACCEPTANCE OF BTS ARMY - Mohamed, Nurul Hamizah; Mohamed, Nurul Hazwani (WILAYAH: The International Journal of East Asian Studies, 2024)
A person can experience a lot of exchange in feelings, different emotions, relationships, loves, and many more throughout their growth. Some of us face failures, traumatic experiences, and downtime that create anxious minds of feeling unworthy and hopeless. Having a role model has been agreed to be helpful in the character development of human beings. In other words, idols affect the admirer’s choices in life matters. Bangtan Sonyeondan (BTS), a seven-member boy band from South Korea, stood up at United Nations in 2018 and spoke about their support for self-love to increase child esteem. However, this campaign is not only successful in being delivered to children but also to youngsters and adults. This effort has greatly impacted their 90 million worldwide fans to be aware of their worth, proud of their own, accept their flaws, and respect differences. In a survey on BTS ARMY, 90% of the participating fans agreed to support the artist until today because they can feel the positive energy from BTS. Even though most of the songs in the albums are made in the Korean language, ARMY understands and can feel the message of the songs clearly. They can react and relate the songs easily to their situation. Fans also gain motivation from speeches, advice, or even idols’ characters. The slogan of LOVE YOURSELF is very straightforward and adaptable to be a value in human lives.